2015
DOI: 10.1007/s11136-015-1084-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender, race, BMI, and social support in relation to the health-related quality of life of cancer survivors: a report from the American Cancer Society’s Study of Cancer Survivors II (SCS-II)

Abstract: The results of this study contribute a unique gender- and racial-specific perspective to cancer survivorship research. While the buffering hypothesis of the stress and coping theory was not supported, the main effects of BMI and social support on HRQoL were different across gender and race.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Overall, increased age, stage and comorbidity quantities were related to worse HRQoL. The tendency for women with bladder cancer to have a lower HRQoL than men with bladder cancer is consistent with some study findings in the general population [30,31,48,49] and in other cancer types [50,51], and also with earlier population studies showing that, on average, women reported a higher proportion of health problems [52].…”
Section: Discussionsupporting
confidence: 89%
“…Overall, increased age, stage and comorbidity quantities were related to worse HRQoL. The tendency for women with bladder cancer to have a lower HRQoL than men with bladder cancer is consistent with some study findings in the general population [30,31,48,49] and in other cancer types [50,51], and also with earlier population studies showing that, on average, women reported a higher proportion of health problems [52].…”
Section: Discussionsupporting
confidence: 89%
“…Social support was a significant theme in our study and is associated with health-related quality of life among cancer survivors [ 27 ]. Cancer survivors lacking a partner are more likely to report poor physical and mental quality of life [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…While much is known on the quality of life of cancer survivors in general, not much is known about the effects of an individual's gender on overall quality of life. Additionally, there are conflicting results as to whether there are gender differences in quality of life (Arden-Close et al, 2011;Giesinger et al, 2009;Geue, et al, 2014;Grant et al, 2011;Kinoshita et al, 2015;Smith et al, 2013;Westby et al, 2016). In the present study, gender as a biological variable was used to measure characteristics of the individual.…”
Section: Conceptual Frameworkmentioning
confidence: 92%